Horizontal Segregation as a Consequence of Hidden Curriculum in Primary School - Gál, Enikő (Central European Journal of Educational Research, 2021)
Much of the special literature deals with examining textbooks, and during their analyses the underrepresentation of women in the world of teaching aids always comes out. The National Curricula (1995, 2003, 2007, 2012, and the new draft of the NC) serve as the basis for writing textbooks, thus it would be worth starting the examination of horizontal segregation according to gender here. In the current study, the goal is to identify and to map theoretical dimensions. This research introduces female education and stereotypes of women in Hungary, their theoretical background as regards horizontal segregation according to gender, and also introduces „hidden curriculum”. Horizontal segregation according to gender in higher education is easily seen, the goal of this study, however, is to examine its presence in primary school education through the teaching of three subjects: music, history, and physics. This dissertation is the first step in the research which furthers the mapping of the theoretical background.